Role of omentin 1 and IL-6 in type 2 diabetes mellitus patients with diabetic nephropathy. Issue 1 (January 2018) - Senthilkumar, Gandhipuram Periyasamy; Anithalekshmi, Melepallappil Sabeenakumari; Yasir, Md.; Parameswaran, Sreejith; Packirisamy, Rajaa muthu; Bobby, Zachariah
Abstract: Aims: Diabetic nephropathy (DN) is one of the major chronic vascular complication of T2DM and leading cause of end-stage renal disease. Inflammation is one of the proposed pathway which explains microvascular complications in T2DM but exact mechanism is still unclear. Omentin-1 is an anti-inﬂammatory adipokine which promotes insulin signaling. IL-6 is a multifunctional cytokine having role in immune and inflammatory responses. The present study was conducted to elucidate the role of omentin-1 and IL-6 in the pathogenesis of DN and its association with insulin resistance. We aimed to assess and compare the serum levels of omentin-1 and IL-6 in T2DM patients with and without DN. Materials & Methods: Our study comprised of 2 groups of 41 each. Group A (controls) included T2DM without nephropathy patients and group B (cases) included T2DM nephropathy patients. Parameters studied were serum omentin-1, insulin, IL-6, fasting blood glucose, urea, creatinine, lipid profile, HOMA-IR, eGFR and BMI. Results & Conclusion: Omentin-1 (p=0.03) was significantly decreased; concomitantly, significant increase in levels of insulin (p=0.004), IL-6 (p=0.023) and HOMA-IR (p=0.0004) were found in cases compared to controls. Bivariate analysis showed eGFR correlating positively with omentin-1 and negatively with insulin in the study population. Our study results, based on serum omentin-1 and IL-6 data suggest important role played by inflammatory mechanism and insulin resistance in the pathogenesis of diabetic nephropathy in type 2 diabetes mellitus patients.